2015
DOI: 10.4103/0974-7796.150493
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic retroperitoneoscopic nephrectomy and partial nephrectomy in children

Abstract: Objectives:The aim was to evaluate our experience in the retroperitoneal laparoscopic approach in total and partial nephrectomies in children.Materials and Methods:We retrospectively reviewed the medical records of 41 patients who underwent retroperitoneal laparoscopic total or partial nephrectomies performed in our center from 2004 to 2012. We looked at the demographic data, age at surgery, indication, operative time, surgical complications, conversion to open surgery and operative complications.Results:Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…They concluded that both methods can be applied in children, but the PPR approach has the added advantage of using two trocars instead of three and is more suitable in patients who require bilateral nephrectomy. Al-Hazmi et al reported their experience in 35 patients who underwent laparoscopic lateral retroperitoneoscopic nephrectomy, the results of which were similar to those of previous studies (17). Valla et al presented their first 100 cases of retroperitoneoscopic lateral nephrectomy.…”
Section: Total Nephrectomysupporting
confidence: 58%
“…They concluded that both methods can be applied in children, but the PPR approach has the added advantage of using two trocars instead of three and is more suitable in patients who require bilateral nephrectomy. Al-Hazmi et al reported their experience in 35 patients who underwent laparoscopic lateral retroperitoneoscopic nephrectomy, the results of which were similar to those of previous studies (17). Valla et al presented their first 100 cases of retroperitoneoscopic lateral nephrectomy.…”
Section: Total Nephrectomysupporting
confidence: 58%
“…The nature and type of fouling depend on the type of material in contact with the tubing – ranging from blood, urine, or medicine to microbe‐laden air – as well as the duration of contact, which can range from a few hours for intermittent‐use urinary catheters to over a year for some long‐term central venous access devices . For urinary catheters, fouling results in an infection rate of 5% per day, requiring patients to undergo recatheterization every 3–8 days to prevent urinary tract infections . In long‐term central venous catheters, the formation of thrombi or the precipitation of incompatible drug mixtures can result in occlusions, leading to pulmonary and other complications as well as increasing the chance of infection .…”
Section: Applicationsmentioning
confidence: 99%
“…The median hospital stay in patients without complications is 3.8 days. [10] In patients with renal arterial embolization, the mean hospital stay is around 2.3 days. [8] Schwartz et al [11] reported their experience in RAE performed in 121 patients over a 12 year period.…”
Section: Discussionmentioning
confidence: 99%
“…Since a non-functioning hydronephrotic kidney has minimal renal parenchyma, the actual incidence of PES is less, around 60%. [9] Coil related complications have also been studied by Capozza et al [10] They performed RAE as an alternative to surgical nephrectomy in 12 children with standard indications for nephrectomy. Revascularization after embolization was reported in one case and they concluded that a post procedure angiogram should be done in all cases to confirm successful embolization.…”
Section: Discussionmentioning
confidence: 99%